Fifth and ninth grade students’ engagement in science classes in Palestine - Marwan Abualrob (South African Journal of Education)
In the study reported on here I aimed to measure the extent to which fifth and ninth grade science students were cognitively, behaviourally, emotionally and socially engaged in science classes. These constructs of engagement were examined based on a set of variables: the grade, students’ gender, teachers’ gender, teachers’ specialisation, teachers’ experience and teachers’ academic degree. To measure these constructs, I used the Wang Engagement Scale as well as a descriptive approach, especially in its relational components. The population, which comprised 15,057 students from the northern West Bank, was divided into groups; from each I chose a representative sample drawn using a random sampling technique based on the size of each of the three directorates of education (Jenin, Qabatia and Tubas). A questionnaire was then designed and delivered to 1,132 respondents from the fifth and ninth grades. The results suggest that fifth graders are by far more engaged than ninth graders, especially female students, and that female teachers, teachers with a degree in science, teachers with 1 to 5 years of experience and teachers with a 2-year associate degree were particularly motivating for student engagement.